Three-Step Fixed Point Iteration for Generalized Multivalued Mapping in Banach Spaces - Zhanfei Zuo (Journal of Applied Mathematics)
The convergence of three-step fixed point iterative processes for generalized multivalued nonexpansive mapping was considered in this paper. Under some different conditions, the sequences of three-step fixed point iterates strongly or weakly converge to a fixed point of the generalized multivalued nonexpansive mapping. Our results extend and improve some recent results.